The Effects of Immigration and Refugee Policies on Social Integration and Community - Ashura, Chiku (Journal of Public Representative and Society Provision, 2021)
This paper emphasizes on explaining the influence of immigration and refugee polices on facets of social integration and community relations in host nations, with special incidences on any difficulties involved by the immigrants/ refugees. The first objective of the study is to analyse these policies’ influence in relation to the subject’s various forms of social, economic and cultural integration, as well as on the state of the examined community. They include survey analysis and interviews with the sample respondents to get first-person narratives of immigrants and refugees’ experience in the United States with the help of phenomenological qualitative research approach with focus on semi-structured interviews and participant observation and focus group methodology. The findings further show that the failure in language, discrimination, and lack of social support are the major sources of non-integration and poor participation of immigrants and refugees in the social and community life, while availability of social support networks is essential for the integration. With these points in mind there is the need to develop policies and support measures for inexpensive language acquisition, anti discrimination arrangements and other educational facilities that can facilitate social inclusion and community integration. It is, therefore, concluded that this research provides a significant contribution towards positive change in the formulation and implementation of social policies aimed at enhancing social inclusion and integration processes in multicultural societies and enhancing community cohesion in the multicultural societies.